2009
DOI: 10.1007/s00264-009-0756-7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of posterior pelvic ring injuries with minimally invasive percutaneous plate osteosynthesis

Abstract: From January 2004 to July 2007, 21 patients with injuries at the posterior pelvic ring were treated with locking compression plate osteosynthesis through a minimally invasive approach and followed up for a mean of 12.2 months. Preoperative and postoperative radiography was conducted to assess the reduction and union. The mean operation time was 60 minutes (range: 40-80). Intraoperative blood loss was 50-150 ml. All patients achieved union at the final follow-up. The overall radiological results were excellent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 27 publications
1
34
0
4
Order By: Relevance
“…In a preliminary clinical study the TIFI has proven to be a system with a low complication rate, as far as iatrogenic vessel or nerve damage [16,23]. In this experimental setting we found that the biomechanical characteristics of the TIFI are comparable to those of established methods.…”
Section: Discussionsupporting
confidence: 61%
“…In a preliminary clinical study the TIFI has proven to be a system with a low complication rate, as far as iatrogenic vessel or nerve damage [16,23]. In this experimental setting we found that the biomechanical characteristics of the TIFI are comparable to those of established methods.…”
Section: Discussionsupporting
confidence: 61%
“…Anatomic reduction and screw position then were checked intraoperatively using AP (Fig. 4) and inlet/outlet view radiographs (15). We performed closed reduction manually, except in two patients in whom a Schanz screw [29] was used as a joystick.…”
Section: Methodsmentioning
confidence: 99%
“…When using posterior open reduction and internal fixation, the range of wound complications varies among studies from 5% to 25% [15,18,32]. Minimally invasive, percutaneous procedures minimize soft tissue injury but the risk of iatrogenic neurovascular lesions is not negligible.…”
Section: Introductionmentioning
confidence: 99%
“…Although this method could also reduce secondary damage to the blood vessels and nerves, it causes the patient discomfort because the steel plate is placed directly under the skin and is palpable (although in the report, they did not receive such complaints from patients); therefore, the authors also believed that the steel plate should be removed after a relatively short period. Moreover, in this fixation method, the steel plate is not tightly attached to the fracture, and the force arm is large; therefore, the fixation is unstable, and there is the possibility of micro-movement in the fracture, which affects fracture healing [17][18][19][20][21]. We treated the 15 patients with pubic ramus MIPO fixation, and with one exception, all of the patients denied discomfort and lived a normal life.…”
Section: Discussionmentioning
confidence: 99%